2004
DOI: 10.1002/bsl.601
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic medication adherence, cocaine use, and recidivism among a parolee sample

Abstract: This study examined the independent and interactive associations between cocaine use and antipsychotic medication adherence in predicting 12 month criminal recidivism among a sample of mentally ill parolees (N = 200). Consistent with prior research, cocaine use (based on hair assays) was associated with more than a threefold increase (relative to non-cocaine users) in the likelihood of a parolee being returned to custody during the follow-up period. Although medication adherence (based on urine specimens) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Other research supports the role of these factors in subsequent difficulties (e.g., recidivism, return to hospital). Medication non-compliance and cocaine use were found to predict recidivism 12 months post-release in a group of parolees with mental health problems who were prescribed antipsychotic medication (Farabee & Shen, 2004). Medication adherence was particularly important in preventing recidivism for consumers of cocaine, reducing the risk of recidivism by 26% (Farabee & Shen, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research supports the role of these factors in subsequent difficulties (e.g., recidivism, return to hospital). Medication non-compliance and cocaine use were found to predict recidivism 12 months post-release in a group of parolees with mental health problems who were prescribed antipsychotic medication (Farabee & Shen, 2004). Medication adherence was particularly important in preventing recidivism for consumers of cocaine, reducing the risk of recidivism by 26% (Farabee & Shen, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, patient outcomes with respect to re-arrest range drastically from 26% of parolees with mental illness returning to prison within 12 months (Farabee & Shen, 2004) to reconviction of 53% of forensic patients receiving care from specialized community forensic services over the longer term (Sahota, Davies, Duggan, & Clarke, 2009). Given the risk of recidivism, the development of effective community support programs for forensic patients is important to reduce recidivism and facilitate independent living in the community.…”
mentioning
confidence: 99%
“…For instance, Hispanic Americans are more likely to support the death penalty for juveniles than are African Americans (Boots et al, 2004). Hispanics are more likely than African Americans are to refrain from illegal drug use while on parole (Farabee & Shen, 2004) and to follow seatbelt laws (Wells, Williams, & Farmer, 2002). In addition to differing attitudes toward complying with laws, a previously cited study by Kravitz and Klineberg (2000) found that Hispanics and Africans Americans differ in their support for laws such as Affirmative Action.…”
Section: Attitudes Toward the Courts And The Law: Hispanics Compared mentioning
confidence: 92%
“…Receipt of psychiatric medications even while using alcohol or other substances is a central tenet of dual diagnosis treatment and may even help clients achieve abstinence (Mueser et al, 2003) or prevent recidivism (Farabee & Shen, 2004). Overall 83% of experimental and 62% of control participants registered receipt of some amount of outpatient medications services (chi-square = 10.76, df = 1, p < .001), including, respectively, 81% and 64% of those with a schizophrenia diagnosis and 79% and 33% of those with a diagnosis of major depression.…”
Section: Mental Health Measuresmentioning
confidence: 99%